2020
DOI: 10.1111/1556-4029.14528
|View full text |Cite
|
Sign up to set email alerts
|

Blast and Aircraft Crash Trauma: A Selection of WWII Cases from the Defense POW/MIA Accounting Agency Laboratory*†

Abstract: This study examines patterns of skeletal trauma in propeller-driven aircraft crashes and blast-related ground loss incidents from WWII. Specifically, descriptions and criteria used to characterize aircraft deceleration-versus blast-related skeletal injuries are examined from 35 recently identified forensic anthropology cases to determine possible diagnostic traits and characterize skeletal trauma associated with these events. Among these cases, blast trauma is more localized within the skeleton and is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 28 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…The data have not been published for ethical reasons. The pattern of skeletal BFT observed in this study is similar to that found in other studies (Byard & Tsokos, 2006; Palmiotto et al, 2020; Wedel & Galloway, 2014; Wiegmann & Taneja, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The data have not been published for ethical reasons. The pattern of skeletal BFT observed in this study is similar to that found in other studies (Byard & Tsokos, 2006; Palmiotto et al, 2020; Wedel & Galloway, 2014; Wiegmann & Taneja, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…This is due to the impact of the body on the ground, which differs from trauma caused by an airplane crash. Few studies are available that report airplane crashes in an archaeological context (Gapert & Rieder, 2013; Palmiotto et al, 2020). Most of these types of studies are reported in forensic literature (Byard & Tsokos, 2006; de Bakker et al, 2018) or consist of recent professional experiences (such as an army helicopter crash in southeast France or previously an airliner crash in the Alps), but patterns observed in soldiers are similar, especially with respect to helicopter accidents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crushing injuries [19,25]; Traumatic amputation [26] Not specified Uncommon spine injuries including Chance fractures, low lumbar burst fractures, and lumbosacral disassociation [19]; Pelvic trauma [27][28][29]; Inverted butterfly fractures to ribs [6]; Localized trauma to portions of the skeleton [30]; One-or-few primary directions of force [30] Projectiles produced from the blast wave, such as shrapnel or fragmented debris, result in secondary blast trauma. Implicit in secondary blast trauma analysis is the large domain of possible overlap in skeletal trauma characteristics compared to gunshot trauma [21].…”
Section: Blast Trauma Phase Skeletal Injuriesmentioning
confidence: 99%